Modern Approach to Improving the Quality Efficiency of Primary Education (Eurasian Journal of Learning and Academic Teaching, 2023)
Improving the quality of Primary Education is essential to lay a solid foundation for the academic and personal growth of children. To achieve this, it can be effective to include modern areas of Education. In this article, we will explore some modern areas that will help improve the quality of primary education.